2022
DOI: 10.1177/10499091221116634
|View full text |Cite
|
Sign up to set email alerts
|

“We Treat Everyone Equally”: Hospice Care Team Members’ Language Use Regarding Sexual and Gender Minority Patients and Caregivers

Abstract: Purpose The way Hospice Care Team (HCT) members talk about patients and caregivers reflects personal attitudes and experiences, training, and broader social and cultural discourse. This secondary analysis examined the framing language professional hospice care providers used when discussing end-of-life care for LGBTQ+ patients and caregivers. Methods Discourse analysis and frame theory informed a secondary, qualitative analysis of focus group data collected with hospice providers (N = 48) in 3 U.S. states rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…34 Despite this, hospice providers may believe that patients’ or caregivers’ LGBTQ + identity is irrelevant to EOL care, or that providers treat all patients and caregivers the same. 21,38 How minority stress may impact the experience of EOL care remains under-examined, and accounts of LGBTQ + caregivers and patients are underrepresented in the literature. 10…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Despite this, hospice providers may believe that patients’ or caregivers’ LGBTQ + identity is irrelevant to EOL care, or that providers treat all patients and caregivers the same. 21,38 How minority stress may impact the experience of EOL care remains under-examined, and accounts of LGBTQ + caregivers and patients are underrepresented in the literature. 10…”
Section: Resultsmentioning
confidence: 99%
“…34 Despite this, hospice providers may believe that patients' or caregivers' LGBTQ + identity is irrelevant to EOL care, or that providers treat all patients and caregivers the same. 21,38 How minority stress may impact the experience of EOL care remains underexamined, and accounts of LGBTQ + caregivers and patients are underrepresented in the literature. 10 Moreover, the complexity of delivering EOL care within patients' and caregivers' homes and personal spaces-and the many new intimacies and intrusions associated with EOL caregiving-may intensify the effects of minority stress.…”
Section: Discussion: Minority Stress and Home Hospice Caregivingmentioning
confidence: 99%
“…13 In addition, the physical environment is important for person-centered care, as it may send unintentional (or intentional) messages regarding attitudes towards LGBTQ + patients. 14 Although prior studies have examined providers' attitudes and beliefs surrounding LGBTQ + patients and caregivers in the context of hospice, 6,15 few have examined the beliefs of palliative care clinicians working with LGBTQ + patients and caregivers in the context of serious illness. 9 Moreover, few studies have accessed the ways in which structural factors such as SOGI data collection and the clinical environment may affect health care delivery to these populations.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can result in inadvertently ignoring important differences in medical history, experiences, availability of social support, and treatment preferences. 6 Such gaps in knowledge of SGM palliative care provision are evident in a study which found that only four out of 24 palliative care trained social service, health, and faith-based providers demonstrated high competency for meeting SGM older adults’ health and social needs. 7 This lack of competence in caring for SGM individuals contributes to health care inequities for this marginalized group.…”
Section: Introductionmentioning
confidence: 99%